(untitled) (Update Dental College Journal, 2022)
Introduction: The study compares the surgical treatment options utilized to treat temporomandibular joint ankylosis at a tertiary level hospital in Bangladesh from 2016 to 2017. Materials and Methods: In this retrospective analysis, 18 patients (28 joints) were studied. History, radiological and physical examinations, and mouth opening were all part of the preoperative and postoperative evaluation. Age, sex, underlying cause, affected joint (s), surgery modality, complications, and follow-up durations were all taken into consideration. The data was analyzed using the SPSS 22.0 statistical software. The degree of mouth opening before and after different surgical techniques in different patient categories was compared using a one-way ANOVA followed by Tuky’s HSD test. Results: Temporomandibular joint ankylosis was found to be in several forms (fibrous, fibro-osseous, and osseous), with trauma (61.11%) being the most common cause. The patients ranged in age from 5 to 30 years old, with females accounting for 55.55% of the total. The mean mouth opening significantly increased from 3.11 mm pre-operatively to 31.17 mm in the first month following surgery (p = 0.00001). In 55.55% of the instances, temporary facial nerve paresis occurred. Conclusions: Temporomandibular joint ankylosis can be successfully managed with early excision of the ankylotic mass, restoration of the ramus height by bone grafting, interpositional arthroplasty, and intensive physiotherapy. Update Dent. Coll. j: 2022; 12(2): 7-13